Intergovernmental relations in a Cordillera Autonomous Region - Rood, Steven (1989)
The article looks into the implications in intergovernmental relations brought about by the creation of an autonomous region in the Cordilleras. National/regional relations in a federal state and in states with autonomous regions are presented as models which bring out a two-fold lesson: the overwhelming powers of the national government, and the political nature of national/regional relations. The models imply that the extent and nature of autonomy will be determined not by formal law but by political interaction. As to regional/local relations, the article points out the need to clarify the governmental unit that should be the proper venue for political action, and the place of tribes, indigenous institutions and non-governmental organizations in the political processes of the region. It also examines the proposed Organic Act and finds many restrictions imposed by Congress. The article asserts that the creation of an autonomous region is merely a new stage in a political struggle and not a triumph of autonomy.
Keywords: Cordillera Autonomous Region; Local autonomy